Development of Strength-Maturity Relationship for Coral Sand Concrete Incorporating Bamboo Leaf Ash - Peter Kavita Nzimbi; Silvester Ochieng Abuodha; Erastus Karoki Kabando; Kiplagat Chelelgo (Advances in Materials Science and Engineering)
In this study, the maturity concept was applied to predict the compressive strength of coral sand concrete incorporating bamboo leaf ash as a cement replacement material. The use of coral sand concrete is restricted due to drawbacks such as low compressive strength, which result from the brittleness and high breakage of coral sand. Therefore, this study sought to evaluate the effect of varying percentages of coral sand on the compressive strength of conventional river sand concrete incorporating bamboo leaf ash as a partial replacement for cement. The coral sand content was varied as a percentage of the total fine aggregate content in amounts of 0%, 10%, 20%, 30%, and 40%. The maximum amount of 40% was chosen to confine the combined fineness of coral and river sand in zone 2 of the gradation curve, which was the zone for the river sand used in the control mix. Bamboo leaf ash was used as a cementitious supplementary material and varied at 0%, 2.5%, 5%, and 7.5% according to the weight of cement. The combined effect of bamboo leaves ash and coral sand on concrete strength development was investigated. To determine the optimal content of coral sand and bamboo leaf ash, 25 mixes were prepared and subjected to compressive strength tests. The mixture containing only river sand and no bamboo leaf ash was the control. Three sets of samples were cured in temperature baths kept at 4°C, 17.5°C, and 40°C. The bath samples were drawn periodically and their compressive strength was tested during a 28-day curing period. It was observed that the early age strength development rate increased with increasing percentage of coral sand. An increase in the amount of bamboo leaf ash was observed to lead to a lower rate of strength development for mixes containing no coral sand. The optimal mix was found to have 40% partial replacement of river sand with coral sand and 5% partial replacement of cement with bamboo leaf ash. The findings were further supported by XRD, SEM, and EDS analyses. The strength-maturity relationship was developed for the optimal mix. Activation energy, datum temperature, and strength gain constant for the optimal mix were determined as per ASTM C 1074. Calibration curves for predicting concrete strengths were developed using logarithmic, modified exponential, modified hyperbolic, and dose-response Hill models. Nurse–Saul and Arrhenius maturity indices were used to develop the compressive strength prediction models. The modified exponential model and the dose-response Hill model were found to have higher accuracy in estimating compressive strengths compared to the logarithmic and modified hyperbolic models which gave poor prediction of compressive strength. Arrhenius maturity function was effective in strength estimation compared to Nurse–Saul maturity function. The results of this study showed promising performance for certain mixtures and hence suggesting potential application in construction projects.